The Routledge companion to spatial history
1 online resource (xvi, 237 pages)
Keywords: "Explores the full range of ways in which GIS can be used to study the past, considering key questions such as what types of new knowledge can be developed solely as a consequence of using GIS and how effective GIS can be for different types of research"--Provided by the publisher.